The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1002/app.55357
|View full text |Cite
|
Sign up to set email alerts
|

Non‐isothermal crystallization kinetic of recycled PET and its blends with PBT modified with epoxy‐based multifunctional chain extender

Andreas Himmelsbach,
Christian Brütting,
Yavuz Akdevelioglu
et al.

Abstract: A fundamental understanding of crystallization behavior is essential for the processing of both virgin and recycled polymers. This research delves into the crystallization characteristics and non‐isothermal crystallization kinetics of recycled polyethylene terephthalate (rPET) and its blends with poly butylene terephthalate (PBT), which have been modified using epoxy‐based multifunctional chain extenders (CE). The preparation of rPET/PBT blends involved a twin‐screw extruder, with varying weight ratios and dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
(218 reference statements)
1
1
0
Order By: Relevance
“…In a previous study, it was demonstrated that when the processed PET/PBT blends are fast-cooled, crystalline phases are immiscible, whereas slow cooling could cause the cocrystallization of PET and PBT, leading to the full miscibility of PET and PBT polymers . The crystallization kinetics of the 25/75 blend sample, which confirms our discussion, is comprehensively studied elsewhere …”
Section: Results and Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In a previous study, it was demonstrated that when the processed PET/PBT blends are fast-cooled, crystalline phases are immiscible, whereas slow cooling could cause the cocrystallization of PET and PBT, leading to the full miscibility of PET and PBT polymers . The crystallization kinetics of the 25/75 blend sample, which confirms our discussion, is comprehensively studied elsewhere …”
Section: Results and Discussionsupporting
confidence: 83%
“…54 The crystallization kinetics of the 25/75 blend sample, which confirms our discussion, is comprehensively studied elsewhere. 94 3.3. Bead Foaming Behavior.…”
Section: Resultsmentioning
confidence: 99%